Characteristics of Type II Diabetes Mellitus Patients in the Elderly in the Work Area of Public health center Harapan Raya Pekanbaru - Zurhayati zuhayati; Nurul Hidayah (UIMA Press, 2021)
Introduction: Specific challenges in the health sector continue to increase as seen from the emergence of increasing degenerative problems and non-communicable diseases in the elderly, one of which is Diabetes Mellitus. Diabetes Mellitus is a chronic disease that is still a major problem in Indonesia. Objectives: To determine the characteristics of Type II Diabetes Mellitus Patients in the Elderly in the Work Area of Public Health Center Harapan Raya Pekanbaru. Methods: A descriptive quantitative study with cross-sectional approach Results: The results of the research conducted using univariate analysis showed that the majority of ages 45-65 were at risk of suffering from Diabetes Mellitus Type II, namely 21 people (70%), the majority of men were at risk of suffering from Type II Diabetes Mellitus, namely 22 people (73.3) and The majority of respondents' education is high, namely 23 people (76.7%). Suggestion It is hoped that health workers will provide information to the public regarding the prevention and treatment of Type II Diabetes Mellitus in the Elderly. Conclusion: The majority of respondents 'ages are at risk, the majority of respondents are male and the majority of respondents' education is high.